Contextual safeguarding and child protection: rewriting the rules - Firmin, Carlene (Routledge, 2020)
"This book offers a complete account of Contextual Safeguarding theory, policy and practice frameworks for the first time. It highlights the particular challenge of extra-familial routes through which young people experience significant harm, such as child sexual exploitation, criminal exploitation, serious youth violence, domestic abuse in teenage relationships, bullying, gang-association and radicalisation"--